2020
DOI: 10.1101/2020.02.21.959387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redundant Trojan horse and endothelial-circulatory mechanisms for host-mediated spread ofCandida albicansyeast

Abstract: The host innate immune system has developed elegant processes for the detection and clearance of invasive fungal pathogens. These strategies may also aid in the spread of pathogens in vivo, although technical limitations have previously hindered our ability to view the host innate immune and endothelial cells to probe their roles in spreading disease. Here, we have leveraged zebrafish larvae as a model to view the interactions of these host processes with the fungal pathogen Candida albicans in vivo. We examin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Candida albicans survive within macrophages and can be released far from the site of infection through non-lytic exocytosis. The intracellular viable yeast is able to get into the bloodstream and use blood flow to transmigrate to other tissues ( Scherer et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans survive within macrophages and can be released far from the site of infection through non-lytic exocytosis. The intracellular viable yeast is able to get into the bloodstream and use blood flow to transmigrate to other tissues ( Scherer et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, massive researches have focused on CNS invasion during fungal meningitis and numerous milestones achieved, including the fact that cryptococcal cells can interact with brain epithelial cells directly and indirectly by microscopy or electron microscope [18][19][20]28]. However, blocking this progression is still on the way.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the raised body temperature, limited nutrients of glucose and metal ions, phagocytosis by phagocytes and cellular immunities are powerful weapons for fungal elimination in hosts [4][5][6][7][8][9][10], while fungal evolved strategies in return, such as temperature resistance, polysaccharide capsule and melanin production, morphology switching, and virulence gene expressions [11][12][13][14][15][16]. Nonetheless, the mechanisms of fungal central nervous system (CNS) invasion have not been determined, which is also a mystery in cryptococcosis, a life-threatening fungal invasive disease, initialized by human pathogen Cryptococcus neoformans [17][18][19][20]. Cryptococcal diseases are predominant prevalent among immune compromised patients, such as HIV/AIDS, organ transplanted, systemic lupus erythematosus, and other immune associated diseases, and contribute about 15% of deaths in HIV/AIDS patients [21][22][23].…”
Section: Introductionmentioning
confidence: 99%